The INFLUENCE OF MARKETING MIX ON THE PURCHASE DECISION OF ELECTRICAL PRODUCTS AT PT SINAR TERANG INTI - Buwono, Andika Pulung (Universitas Ciputra Surabaya, 2022)
This study aims to determine how the significant influence of Product, price, Place, Promotion on the service Products of PT SINAR TERANG INTI. The factors studied are Product (X1), Price (X2), Place (X3). The population in this study were all final consumers of PT. PLN (Persero) UP3 Mojokerto whose number is known for sure (finite). The sample in this study used purposive sampling, which is a sampling technique with certain criteria.